Question

Asked Jan 20, 2019

24 views

Solve for x 2/x-2+2/x^2-4=3/x+2

Step 1

The given statement says to solve for x, and the given equation is,

Step 2

Since, x^{2} – 4 = (x – 2) (x + 2),

Substituting in the above equation

Step 3

Taking 2/(x-2) common and...

Tagged in

Q: The graph of a function is given. Determine whether the function has an inverse function. Does the g...

A: This graph satisfies vertical line test.

Q: (2-4i)(5-7i) =

A: The steps of simplification are shown on board. Here we se the result i^2 =-1 and then collect the ...

Q: Explain how f (x) = (x − 1)2 + 3 is obtained from f (x) = x2

A: The given functions are f(x) = (x-1)2 +3 and f(x) = x2.Sketch the graph of the functions f(x) = (x-1...

Q: Condense the expression to the logarithm of a single quantity (c) 4 [lnz +ln(z +5)] −2ln(z −5)

A: Consider the provided expression.

Q: 2x+7 The function x-9 X#9, is one-to-one. Find an equation for f (x), the inverse function. 0)x2 (Si...

A: Consider the given one-to-one function:

Q: 35) Complete the table below to create an odd function f. x 60 246 3 -12 f(x)

A: Given:The function is an odd function.That is, f(-x) = -(f(x)).

Q: Given the following function (a) find the vertex (b) determine whether there is a maximum or a minim...

A: Note: This question consists of 4 sub parts, we are authorized to answer up to 3 subparts, so we are...

Q: Graph the hyperbola (y+3)2/16-(x+6)2/4=1

A: The given equation is (y+3)2/16-(x+6)2/4=1.

Q: Does the relation y(x + y) = 1 specify a function? Explain.

A: From y(x+y)=1 we try to solve for y first. Used the quadratic formula to solve for y.